2023
DOI: 10.1002/fsn3.3387
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of chocolates with high‐value‐added plant‐based substances: Recent trends, current challenges, and future prospects

Amirhossein Abedini,
Samira Dakhili,
Sara Bazzaz
et al.

Abstract: High consumption of delicious foods, such as chocolates, is considered excellent snacks, capable of converting from health‐threatening to great functional foods. The fortification of chocolates with high‐value‐added plant‐based substances might improve their healthful effects, nutritional properties, and shelf life. Chocolate could be an effective carrier for plant‐based substances delivery, and it could be an effective vehicle to treat and reduce the indications of disease, such as obesity, overweight, hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 104 publications
(103 reference statements)
0
0
0
Order By: Relevance
“…Comprehensive reviews have explored the potential biological activity, processing techniques, and fortification approaches used to enrich chocolate with bioactive compounds. 75,76 These reviews provided valuable insights into the mechanisms and potential health effects of enriched chocolate consumption.…”
Section: Future Perspectives and Limitationsmentioning
confidence: 99%
“…Comprehensive reviews have explored the potential biological activity, processing techniques, and fortification approaches used to enrich chocolate with bioactive compounds. 75,76 These reviews provided valuable insights into the mechanisms and potential health effects of enriched chocolate consumption.…”
Section: Future Perspectives and Limitationsmentioning
confidence: 99%
“…Previous studies have indicated that the maceration process can change the profile of bioactive compounds in grape pomace, and therefore influence the antioxidant activity [33,34]. The processing, especially when it involves lengthy thermal treatment and/or high shear, can also impact the antioxidant and anticancer activities of chocolates, because using high shear and thermal treatment during processing may have negative effects on the polyphenols which are considered the main source of antioxidants and anticancer agents [35]. Chocolates typically required a lengthy conching process, which subjects the ingredients to repeated crushing or shear and relatively high temperature (49-82 • C) for 12-96 h, to reduce particle size and develop flavors [36].…”
Section: Introductionmentioning
confidence: 99%